“My Compliments to your Dressmaker”: The Past and Future of Wearable Tech. - Swanstrom, Lisa (Science Fiction Studies, 2021)
The article discusses the integration of fashion in science fiction, such as the dress worn by the character of Dr. Miranda Jones played by Diana Muldaur in the fifth episode of the third season of the original television series "Star Trek." Topics include the description of the dress, the garment's museum exhibitions devoted to Star Trek fandom, and comments on anticipatory impulse in a variety of popular fashion lines.